![\frac{x+1}{2}= \frac{2x-3}{5}+2
\frac{x+1}{2}= \frac{2x-3}{5}+2](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%2B1%7D%7B2%7D%3D+%5Cfrac%7B2x-3%7D%7B5%7D%2B2%0A++)
избавляемся от знаменателя *10
(x+1)*5=(2x-3)*2+2*10
5x+5=4x-6+20
5x-4x=20-6-5
x=9
![\frac{11-3x}{4} = \frac{x+13}{6} -x \frac{11-3x}{4} = \frac{x+13}{6} -x](https://tex.z-dn.net/?f=+%5Cfrac%7B11-3x%7D%7B4%7D+%3D+%5Cfrac%7Bx%2B13%7D%7B6%7D+-x)
избавляемся от знаменателя *12
(11-3x)*3=(x+13)*2-12*x
33-9x=2x+26-12x
12x-9x-2x=26-33
x=-7
![\frac{5x+8}{9}+x= \frac{7x+10}{6} \frac{5x+8}{9}+x= \frac{7x+10}{6}](https://tex.z-dn.net/?f=+%5Cfrac%7B5x%2B8%7D%7B9%7D%2Bx%3D+%5Cfrac%7B7x%2B10%7D%7B6%7D++)
избавляемся от знаменателя *18
(5x+8)*2+18*x=(7x+10)*3
10x+16+18x=21x+30
10x+18x-21x=30-16
7x=14
x=14/7
x=2
![\frac{2*(2-3x)}{5}+1= \frac{3-4x}{3} \frac{2*(2-3x)}{5}+1= \frac{3-4x}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B2%2A%282-3x%29%7D%7B5%7D%2B1%3D+%5Cfrac%7B3-4x%7D%7B3%7D++)
избавляемся от знаменателя *15
3*2*(2-3x)+15*1=(3-4x)*5
6*(2-3x)+15*1=(3-4x)*5
12-18x+15=15-20x
20x-18x=15-15-12
2x=-12
x=-12/2
x=-6